The interior inverse spectral problem for differential pencils with the conformable fractional derivative - Khalili, Yasser; Koyunbakan, Hikmet (Springer Heidelberg, 2026)
In this article, we consider a fractional differential pencil with the conformable derivative and spectral boundary conditions. The inverse problem is studied and it is shown that potentials and boundary conditions are uniquely determined by one spectrum together with a set of values of eigenfunctions at x=c alpha.\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$x =c_{\alpha }.$$\end{document}
Keywords: Interior inverse problem; Conformable; Pencil; Spectrum